Dengue death rate higher among women than men in Bangladesh - Roney, Miah; Mohd Fadhlizil Fasihi, Mohd Aluwi (Bangladesh Infection Research Association, 2024)
Bangladesh saw a dengue epidemic in 2023 that resulted in a significant number of illnesses and fatalities throughout the country. The Directorate General of Health Services (DGHS) reports that there were 3,21,179 confirmed cases of dengue from January to December 2023, with a fatality rate of 0.53%. Most cases and fatalities in 2023 were documented from June to December. In Bangladesh, the prevalence of dengue fever is greater in men than in women, but women also die from the disease at a higher rate than in men. Given the atypical seasonality of the epidemic and the sudden spike in cases early on, it is noteworthy that mosquito and potential hotspot densities were at an all-time high throughout the previous years.